VALIDITAS BAHAN AJAR FISIKA SISWA SMA/MA BERBASIS CONCEPTUAL CHANGE - Febriani Hastini Nasution; Dedes Asriani Siregar (Jurnal Education and Development, 2019)
This article was contained about analyzing the validity of students’ teaching module based on conceptual change. Students’ teaching module based on conceptual change was the module which is arranged based on the indicator of conceptual change, they are elicit and confirm current ideas, exposure to conflicting evidence, construct new explanation, apply and evaluate new explanation, and the last is review change in ideas and explanations. This module was validated by three validators. There were four components which was validated, they were about content validity which is consist of the components of module and the appropriateness of module’s contents, construct validity, language validity, and the suitability with the learning used conceptual change. Based on analysis data obtained: The average value of validity of students’ teaching module by three validators was 91.11 was in very valid category. Furthermore, the value of each components were 94.90 in content validity, 90.97 in construct validity, 86.90 in language validity, and 91.67 in the suitability with the learning used conceptual change. Four of the components were in very valid category.